Numerical investigation of the flow characteristics inside a supersonic vapor ejector - Hamza K. Mukhtar; Ahmed Fadlalla; Rania Ibrahim; Saud Ghani (International Journal of Thermofluids)
Integrating a vapor ejector with an air-cooled absorption cooling system (ACS) requires understanding how the ejector responds to varying condenser conditions and how the geometrical parameters affect the system's performance. This study provides a numerical investigation of the flow characteristics inside supersonic vapor ejectors. The primary objectives were identifying the best nozzle design for ACS and explaining how the secondary flow responds to different back pressures. The developed model was validated against experimental data and a one-dimensional model. Despite exhibiting increased flow fluctuations, the convex nozzle achieved an entrainment ratio of 0.4. This value was 4.9 % and 7 % higher than the values obtained by the straight and the concave nozzles, respectively. In contrast, the concave nozzle exhibits better flow stability and pressure recovery, which are considered appealing for the air-cooled ACS. The straight nozzle emerged as a balanced alternative, offering moderate entrainment alongside favorable flow stability. Moreover, secondary flow behavior at different operating modes was elaborated. Secondary flow choked at back pressures between 60–70 kPa, indicating optimal entrainment. However, at 75–80 kPa, while the secondary flow was entrained, it failed to reach sonic speed due to high-pressure waves, resulting in the sub-critical condition. Further increases in back pressure to 85–90 kPa induced back-flow due to elevated local static pressure. Mach number profiles at the mixing tube entrance remained consistent under critical operation but deviated post-critical back pressure, reflecting altered flow characteristics downstream of the mixing tube. Such elaboration of flow dynamics within ejectors paves the way for innovative designs of vapor ejectors, potentially developing ACS.